The significance of note-taking skills for office management professionals / Nurfaznim Shuib and Nurul Izzati Idrus - Shuib, Nurfaznim; Idrus, Nurul Izzati (Universiti Teknologi MARA, Kedah, 2023)
In the fast-paced and technology-driven world of the modern office, effective communication and information management are vital for success. Among the essential skills that have stood the test of time and continue to be relevant today is note-taking. The ability to capture, organize, and retain information through note-taking remains an indispensable tool for professionals in various industries. In addition, the way individuals take notes and handle information has significantly changed in the digital era. Pen and paper and other conventional note-taking techniques have coexisted alongside more recent technology advancements like voice recognition software, cloudbased platforms, and note-taking applications. Such change in note-taking habits has created several important issues and possibilities that must be addressed to improve the information management process. Conversely, employers also send employees to courses from time to time to learn these note-taking skills, which can improve the efficiency of doing documentation typing tasks in the office.